Association of lifestyle factors with sarcopenia: Systematic Review - Domínguez-Chávez, Claudia Jennifer; Rosales-Garza, Rosana Berenice; Aguilar-Arámbul , Sayra Cecilia; Mata-Reyes, María Del Carmen; Monfil-Bautista, Julissa; Mendoza-Catalán , Geu (Horizonte Sanitario, 2022)
Objective: To identify the association between the factors of nutrition, physical activity, alcohol consumption, tobacco and sleep with sarcopenia in older people. Materials and methods: A search of the available evidence was carried out in the Dialnet, Science Direct, Scielo, and PubMed databases. For the search strategies, the terms in Spanish and English were considered, according to the Descriptors in Health Sciences and the Medical Subject Headings. The Boolean operators "AND" and "OR" were used. A total of 21 studies were analyzed and synthesized. Results: It was identified that the consumption of nuts, fruits and omega three may be associated with a lower probability of developing sarcopenia. Staying active suggests a lower probability of sarcopenia, in contrast, sedentary older people have higher risks. Alcohol consumption is a factor that is associated with a higher probability of generating sarcopenia in women. In most studies, tobacco use shows no significant association with sarcopenia. Regarding sleep, it is reported that sleeping less than 6 hours or more than 8 hours can increase the probability of presenting sarcopenia in women. Conclusions: It is ideal to consider the timely identification of these risk factors that are present in the lifestyle, and that are likely to be modified during the stages prior to old age.Keywords: Nutrition of the elderly; Physical exercise; Alcoholism; Tobacco use; Sarcopenia